2016
DOI: 10.1111/jppi.12144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vocational Training on a Group of People with Intellectual Disabilities

Abstract: Intellectual disability (ID) is the most restraining disability for professional inclusion, mainly due to the lack of adaptive skills focused on the work environment observed in people with ID. The aims of this study were (i) to describe and analyze the effects of a vocational training program on the adaptive behavior of people with ID and (ii) to evaluate the social impact of employability on the life of the employees with ID. Participants were 43 people with mild or moderate ID, age between 18 and 28 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…The support needs scores have been used to assess the effectiveness of six interventions [ 51 , 62 , 68 , 73 , 74 , 92 , 108 ], focused on the development of life skills or related to employment. Of these, only Tate et al (2019) found no effect on support needs, as assessed through CANS, after applying a coaching program for transition to adulthood to youths with brain injury [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The support needs scores have been used to assess the effectiveness of six interventions [ 51 , 62 , 68 , 73 , 74 , 92 , 108 ], focused on the development of life skills or related to employment. Of these, only Tate et al (2019) found no effect on support needs, as assessed through CANS, after applying a coaching program for transition to adulthood to youths with brain injury [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…With reference to employment, Gomes-Machado et al (2016) assessed the effects of a vocational training program on the adaptive behavior and employability skills of 43 youths with intellectual disabilities, obtaining a 50% reduction of support needs in various areas [ 51 ]. Finally, Wehman et al (2016) evaluated an employment program for 49 youths with intellectual disability and autism, obtaining meaningful reductions in support needs over the control group after 3 and 12 months of intervention [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vocational training and other forms of formal training contribute to the employment success of individuals with disabilities (Dutta et al, 2008;Heloísa et al, 2016;Thoresen, Cocks, & Parsons, 2019). A degree gives access to recognised occupations that require occupation-specific skills, which in general are better paid and more secure in terms of the type of contract (Wolbers, 2003).…”
Section: Hypothesismentioning
confidence: 99%
“…To our best knowledge, none of the investigated interventions were generalized to a wider range of people with intellectual disabilities with different self‐management goals. Previous research focused, for example, on prompting (Bouck, Satsangi, & Bartlett, ; Dollar et al., ; Wu, Wheaton, & Cannella‐Malone, ), the use of technology (Cannella‐Malone et al., ; Cavkaytar, Acungil, & Tomris, ; Cullen, Alber‐Morgan, Simmons‐Reed, & Izzo, ; Douglas, Ayres, & Langone, ; Ramdoss et al., ), employment (Gilson, Carter, & Biggs, ; Gomes‐Machado, Santos, Schoen, & Chiari, ) or health behaviour (Taggart et al., ; Wilson & Goodman, ). Most studies presented promising results, but drawing firm conclusions about the effects of self‐management interventions is difficult due to studies’ narrow focus and methodological limitations.…”
Section: Introductionmentioning
confidence: 99%